Two different faces of Cavafy in English: A corpus-assisted approach to translational stylistics - Pantopoulos, Iraklis (International Journal of English Studies, 2012)
A translator is seen to leave a personal mark on the text through their stylistic choices and the patterns formed by these choices. This article comprises a case study that uses a specialized comparative corpus containing translations of C.P. Cavafy's canon in order to explore the distinctive stylistic features of Rae Dalven and of Edmund Keeley and Philip Sherrard (working in collaboration), in both quantitative and qualitative terms. Exploring the different approaches to Cavafy's poetry on the stylistic level reveals the stylistic fragmentation of the poet after crossing over into a dominant language and literary market. Overall word frequencies for each translation are examined, the stylistic features that are prominent in each case are identified, and their significance is considered. Special attention is also paid to the way a stylistic feature belonging to the ‘universal aspects of literature’ is treated by each translator. By foregrounding the translators and their distinct choices, the “homogenization” effects that often characterize translation into a major language are arrested. Instead, the focus falls on the factors that shape each translator's use of language and their impact.